Kritik Terhadap Keadilan Ekonomi Kontemporer dan Hukum Ekonomi Syariah dalam Tradisi Tompangan - Suaidi, Suaidi; Sodiqin, Ali; Rozaki, Abdur (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The tradition of tompangan, which was originally a form of social solidarity between residents, has shifted into an informal debt system, with returns exceeding the initial amount given, thus causing injustice and economic inequality. This study discusses the critique of contemporary economic justice and the relevance of Sharia Economic Law to the shift in the tradition of Topangan in Madura. This study uses a qualitative approach with data obtained through interviews and observations. The results of the study indicate that social change and modernization have shifted the traditional value of tompangan, which was originally a grant, into a qardh (debt) contract that tends to be capitalistic. Based on the perspective of Sharia economic law, returns that exceed the amount of the loan can be categorized as usury which is prohibited in Islamic law. This study also found that the community still considers this practice socially legitimate despite the uncertainty and injustice in the return of tompangan goods. Therefore, combining insights from the tompangan tradition with contemporary economic justice theory can open up new perspectives for economic policies that are fairer and more responsive to the needs of local communities and in line with the principles of Sharia economic law.